Spatial Autocorrelation of Population Density, HIV/AIDS, and Diabetes Mellitus with Pulmonary Tuberculosis in Kupang, East Nusa Tenggara, Indonesia - Lengari, Maria; Weraman, Pius; Syamruth, Yendris K; Ruliati, Luh Putu; Adu, Apris A (Indonesian Journal of Medicine, 2025)
Background: The 2023 Global Tuberculosis (TB) Report ranks Indonesia second in the world for TB cases, with approximately 1,060,000 new cases and 134,000 deaths annually—equating to 17 deaths per hour. In East Nusa Tenggara (NTT) Province, pulmonary TB cases increased from 5,361 in 2020 to 5,184 in 2021, and significantly rose to 8,035 in 2022. Kupang Regency reported the highest number of TB cases in 2022. This study aimed to analyze the impact of risk factors, including population density, HIV/AIDS, and Diabetes Mellitus, on pulmonary TB cases using spatial analysis with the GeoDa application. Subjects and Methods: This ecological study, conducted in Kupang, Indonesia, between October and November 2024, uses secondary data from 2021 to 2023 as the research sample. The study includes all recorded pulmonary TB patients from the Kupang Health Office, with 441 cases in 2021, 785 cases in 2022, and 979 cases in 2023. Results: The Local Indicator of Spatial Association (LISA) test results show a low-high spatial relationship between HIV and TB variables in the Maulafa district for 2022-2023. Additionally, the diabetes mellitus (DM) and TB variables exhibit a High-Low spatial pattern in 2021 and a Low-High pattern in 2022 within the district. Regarding population density in 2021, a clustered spatial autocorrelation was observed (p-value = 0.049 < 0.05; [I] = 0.051 > E[I] = -0.200; Mean = 0.116; SD = 0.120), with a High-Low pattern in the Kota Lama district and a Low-Low pattern in Maulafa. From 2022 to 2023, a Low-High spatial pattern was identified in the Maulafa district. Conclusion: The results of this study indicate spatial autocorrelation between population density and pulmonary TB cases in Kupang City in 2021. However, from 2022 to 2023, no spatial autocorrelation was observed, and the same pattern was found for Diabetes Mellitus and HIV/AIDS.